Analysis of Website Usability of Provincial Governments in Indonesia with The Heuristic Evaluation Method - Vica Akhira Fitra Moersahit; Andhika Giri Persada (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The Indonesian government initiated the implementation of E-government as a public service in 2003 with Presidential Instruction No.3 of 2003 issuance of National Policy and Strategy for E-Government Development. This rule was strengthened in 2007 by Regulation of the Minister of Communication and Information Technology No.41/PER/M.KOMINFO/2007 concerning General Guidelines for National Information and Communication Technology Governance. However, many provincial government sites still have not implemented a usability test. This problem is reinforced by the website interface not meeting the standards set by the government. So, usability testing is needed to find the problems found on the provincial government website. The method used in this usability test is the heuristic evaluation method. The evaluation was carried out by involving three evaluators to evaluate 28 provincial government sites. The evaluator detects problems based on ten heuristic principles proposed by Jakob Nielsen and is assessed with a severity rating. analysis results show the province of Aceh and the Special Region of Yogyakarta website is ranked first with the lowest severity rating value with a value of 0.43. In contrast, North Kalimantan is ranked last with the highest severity rating value with a value of 1.08. Around 71.4% of provincial government websites have no problems with user control & freedom, and consistency & standards. Then half of the provincial government's websites have problems with recognition rather than recall. Last, more than 50% of websites have problems with other heuristic principles.